Prohibition Excessive in Worship: Analysis of Hadith from Muslim History in the Shahih Book No. 1159 - Athiyatul Maziyah; Abdul Karim Amrullah; Viki Junianto; Farhan Ali Ishaqi (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study discusses and analyzes a hadith from Sahih Muslim, numbered 1159, in his authentic collection. This hadith addresses the Prophet's prohibition directed toward a companion who continuously engaged in worship to the extent of neglecting his family’s rights and the rights of others. The aim of this research is to establish the hadith's level of authenticity (